2005
DOI: 10.1002/marc.200500150
|View full text |Cite
|
Sign up to set email alerts
|

A Catalytic Approach to Functional Poly(1,4‐ketone)s Bearing Pendant Monosaccharide Fragments

Abstract: Summary: Novel alternating polyketone‐based polymers bearing pendant saccharide units that are accessible by polymerization catalysis are presented. The materials were synthesized by polymerization of carbon monoxide and α‐olefins containing protected glucose or N‐acetyl glucosamine residues. The dicationic PdII bis(phoshine) complex [Pd(dppp)(NCCH3)2](BF4)2 was used as a catalyst precursor. An O‐deacetylation of the copolymers afforded materials with amphiphilic character.Structure of the poly(1,4‐ketone) cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The chemical structures of the obtained products were confirmed by 13 C and 1 H NMR and IR spectroscopies. The three signals attributable to the carbonyl groups of the main chain (head-head, head-tail, and tail-tail enchainment) in 13 C NMR spectrum proved the regioirregularity of the oligomers.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The chemical structures of the obtained products were confirmed by 13 C and 1 H NMR and IR spectroscopies. The three signals attributable to the carbonyl groups of the main chain (head-head, head-tail, and tail-tail enchainment) in 13 C NMR spectrum proved the regioirregularity of the oligomers.…”
Section: Resultsmentioning
confidence: 91%
“…Since there are only a limited number of examples of functional polyketones reported, these copolymerizations are challenging experiments. The first successful attempt was the synthesis of polyketones containing pendent monosaccharides . The surprising tolerance shown by the catalytic system toward the glycosylated monomers prompted us to perform copolymerization experiments with CO and alkenes substituted with amino acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbonyl groups give an opportunity for further functionalization through chemical derivatization [27]; to enhance the biocompatibility of polyketones, bioactive moieties, e.g. amino acids or monosaccharides, can be integrated in the polymer chain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Drent et al used a catalyst consisting of Pd(OAc) 2 and DPPP for the co‐ and terpolymerization of CO with functionalized olefins such as methyl undec‐10‐enoate, undec‐10‐enoic acid, undec‐10‐en‐1‐ol, but‐3‐en‐1‐ol, allyl acetate, and 6‐chloro‐1‐hexene 46. Rieger et al reported that a preformed dicationic Pd complex, [Pd(DPPP)(CH 3 CN) 2 ](BF 4 ) 2 , is an effective catalyst precursor for using functionalized allylbenzene derivatives,47 highly functionalized olefins bearing a benzo‐15‐crown ether,48 mesogenic units,49 monosaccharide,50 amino acids, and steroids 51. A dicationic palladium complex bearing 1,10 phenanthroline was employed for the terpolymerizations of undec‐10‐enoic acid or undec‐10‐en‐1‐ol with styrene and CO 52.…”
Section: Copolymerization Of Polar Vinyl Monomers With Carbon Monomentioning
confidence: 99%